Bank leverage cycles and the external finance premium - Ansgar Rannenberg (Deutsche Bundesbank, 2013)
By combining the approaches of Gertler and Karadi (2011) and Bernanke et al. (1999), I develop a DSGE model with leverage constraints both in the banking and in the non-financial firm sector. I calibrate this full model to US data. In a world with only a monetary policy and a productivity shock, the full model matches the relative volatility of the external finance premium, while a BGG model generates too low volatility. The full model also matches the procyclicality of bank leverage, unlike the GK model. For a reasonably calibrated combination shocks to the net worth of banks and non-financial firms, the model reproduces a substantial share of the contraction (increase) of investment (the external finance premium) observed during the Great Recession.
Keywords: E50; E52; 330; leverage cycle; bank capital; financial accelerator; output effects of financial shocks